Anti-inflammatory effect of a flavonoid-rich extract of orange juice in adult zebrafish subjected to Vibrio anguillarum-induced enteritis. Issue 23 (2nd December 2021) - Cirmi, Santa; Randazzo, Basilio; Russo, Caterina; Musumeci, Laura; Maugeri, Alessandro; Montalbano, Giuseppe; Guerrera, Maria Cristina; Lombardo, Giovanni Enrico; Levanti, Maria
Abstract: Inflammation-related pathologies remain a serious health problem with high costs for the community. Citrus flavonoids are known to possess important pharmacological properties, including anti-inflammatory activity. In this study we evaluated the effects of a flavonoid-rich extract of orange juice (OJe) in an experimental model of enteritis induced by Vibrio anguillarum in adult zebrafish ( Danio rerio ). Administration of V. anguillarum through live feed ( Artemia nauplii) for three consecutive days caused evident signs of enteritis in zebrafish. Three days of treatment with OJe before the pathogenic insult resulted in a remarkable reduction of tissue inflammatory events as well as a molecular down-regulation of the inflammatory genes such as IL-1β, IL-6 and TNFα. Our data suggest that OJe counteracts the inflammation of zebrafish intestinal mucosa, indicating that the pool of flavonoids present in orange juice could be useful for the prevention of enteritis. Graphical Abstract: